1999
DOI: 10.1046/j.1440-1754.1999.00333.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of invasive pneumococcal disease in Sydney children, 1991–96

Abstract: The incidence of childhood invasive pneumococcal disease in Sydney was stable during 1991-96 and comparable to rates reported from other industrialized countries. There was no evidence of any change in pneumococcal disease incidence with reduction in invasive Haemophilus influenzae type b (Hib) disease following introduction of Hib immunization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 21 publications
4
10
0
Order By: Relevance
“…Although children and families have very good access to primary health care and to care for severe disease, this study was not designed to enroll children who presented to outpatient clinics, and considering the underutilization of lumber punctures, the incidence rates found in this study may underestimate the total burden of IPD and Hib disease. The estimated incidence rate of childhood IPD reported in our study is within the range of reported incidence rates from population-based studies among nonindigenous Australians, as well as studies performed in the United Kingdom and Israel, but are somewhat higher than the rate reported in a Hong Kong study [24][25][26][27]. The incidence of Hib disease reported in this study is somewhat higher than the incidence of Hib meningitis calculated using the Hib rapid disease burden assessment tool for Vietnam in 2006 (18 cases per 100,000 children aged !5 years) and is somewhat higher than the incidence reported for Hib meningitis in Hanoi (12 cases per 100,000 children aged !5 years) [15].…”
Section: Discussionsupporting
confidence: 79%
“…Although children and families have very good access to primary health care and to care for severe disease, this study was not designed to enroll children who presented to outpatient clinics, and considering the underutilization of lumber punctures, the incidence rates found in this study may underestimate the total burden of IPD and Hib disease. The estimated incidence rate of childhood IPD reported in our study is within the range of reported incidence rates from population-based studies among nonindigenous Australians, as well as studies performed in the United Kingdom and Israel, but are somewhat higher than the rate reported in a Hong Kong study [24][25][26][27]. The incidence of Hib disease reported in this study is somewhat higher than the incidence of Hib meningitis calculated using the Hib rapid disease burden assessment tool for Vietnam in 2006 (18 cases per 100,000 children aged !5 years) and is somewhat higher than the incidence reported for Hib meningitis in Hanoi (12 cases per 100,000 children aged !5 years) [15].…”
Section: Discussionsupporting
confidence: 79%
“…Our results support this possibility. However, it should be noted that with higher numbers ( n = 320) a recent study by Liddle et al reported no evidence of any change in pneumococcal disease incidence, although their study included only a short time period after the introduction of Hib immunisation 23 …”
Section: Discussionmentioning
confidence: 89%
“…In Europe, the rates are 42.1 in Great Britain, 24.2 in Finland, and 10.1 population in Germany 1416. In Australia, it is 12.7 17. Locally in Saudi, the reported rate is 3.4-53.5 population 18…”
Section: Discussionmentioning
confidence: 99%